Extent of Adaptability of Modern Agricultural Technologies by Rural Women at Samastipur District of Bihar - Arunima Kumari and Pooja Kumari, (Indian Journal of Extension Education, 2016)
The prosperity and growth of a nation depends on the position and development of its females, as they not only constitutenearly half of its population but also positively influence the growth of remaining half of population. It is only womenaround whom the whole families growth rotates. The present study was conducted in samastipur district of Bihar with 100respondents to find out the extent of adoption of improved technologies by rural women farmers. The study revealed thatrural women were adopting post-harvest technologies more than the pre-harvest technologies and their adoption wasaffected by their knowledge level.